Identifying rhizosphere bacteria and potential mechanisms linked to compost suppressiveness towards Fusarium oxysporum - Hildah Amutuhaire; Adi Faigenboim-Doron; Judith Kraut-Cohen; Jonathan Friedman; Eddie Cytryn (Environmental Microbiome)
Abstract Background Soilborne fungal phytopathogens pose a significant threat to global food security. While chemical control remains an effective method for managing these pathogens, increasing regulations due to health and environmental concerns, along with rising fungicide resistance, have restricted their use, underscoring the urgent need for sustainable alternatives. The use of compost to enhance soil fertility and suppress plant diseases is well documented. Several studies have underlined the role of microorganisms in disease suppression, but the mechanisms facilitating this disease suppression remain unclear. We evaluated the impact of compost amendment on the composition and functional capacity of the rhizosphere microbiome in cucumber plants (Cucumis sativus) inoculated with Fusarium oxysporum f. sp. radicis-cucumerinum (FORC) under controlled greenhouse conditions using amplicon sequencing, shotgun metagenomic and culture-based techniques. Results Compost amendment significantly reduced FORC-induced disease in cucumber relative to non-amended treatments. While FORC inoculation resulted in significant shifts in microbial (bacterial and fungal) community composition in the rhizosphere of non-amended plants, this phenomenon was substantially less pronounced in the rhizosphere of compost-amended plants. Specifically, compost amendment sustained the presence of Actinomycetota (Streptomyces, Actinomadura, Saccharomonospora, Pseudonocardia, Glycomyces, Thermobifida) and Bacillota (Planifilum, Novibacillus) in FORC inoculated plants, that diminished significantly in inoculated plants without compost. These taxa contained a myriad of non-ribosomal peptides and polyketides synthetases biosynthetic gene clusters (BGCs) with putative antimicrobial and iron-chelating functions. We successfully isolated two Streptomyces strains from FORC-suppressing compost amended rhizospheres that were almost identical to the Streptomyces bin2 (99% ortho ANI) metagenome assembled genome identified in the shotgun metagenome analysis. These strains produced extracellular metabolites that inhibited growth of FORC in-vitro and contained BGCs that encode for compounds with potential antimicrobial capacity. Conclusions Based on results presented in this study, we demonstrate that compost alleviates FORC-induced dysbiosis of the rhizosphere microbiome, maintaining abundance of specific bacterial taxa. These bacterial groups may contribute to disease suppression through a myriad of mechanisms including iron chelation and production of fungal antagonizing secondary metabolites.